MODAL SOSIAL KELOMPOK MINA BAHARI DALAM MENGATASI EKONOMI KOMUNITAS NELAYAN PESISIR BAGAN PERCUT SEI TUAN - Putri Sofia Anjani; Nirzalin Nirzalin; M. Husen MR; Rizki Yunanda (Program Studi Sosiologi Universitas Malikussaleh, 2022)
This study examines social capital in the Mina Bahari fisherman group, Bagan Percut Coastal Village, Percut Sei Tuan District, Deli Serdang Regency. The Mina Bahari group who has social capital in their daily lives and uses it as a tool to survive. This study uses a qualitative method. The purpose of this study is to describe the description of social capital in the Mina Bahari fisherman group in overcoming socio-economic problems. Data collection was carried out in April 2022 by conducting in-depth interviews with informants consisting of the head of the Mina Bahari fishing group, members of the Mina Bahari fishermen, the Head of Percut Village, the Marine and Fisheries Service and the surrounding community. The results show that social capital plays an active role in problem solving, survival and adaptation in fishing groups in the Bagan Percut Coast. Sustainability of adaptation is seen from the coping strategy through contributions in the group which is a means to realize concern among fellow members, cooperation in helping fellow members, a sense of trust, values and norms that apply in the group. In addition, fisherman groups also build social networks with village governments and from the Marine and Fisheries Service in overcoming poverty in fishing groups with various activities.Penelitian ini mengkaji tentang modal sosial pada kelompok nelayan Desa Pesisir Bagan Percut Kecamatan Percut Sei Tuan Kabupaten Deli Serdang. Kelompok yang memiliki modal sosial dalam kehidupan dan menjadikan sebagai alat untuk bertahan hidup. Tujuan dari penelitian adalah memaparkan deskripsi modal sosial pada kelompok nelayan Mina Bahari dalam mengatasi sosial ekonomi. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa modal sosial berperan aktif dari kepercayaan, norma dan jaringan sosial dalam penyelesaian masalah, keberlangsungan hidup dan adaptasi dalam kelompok nelayan di Pesisir Bagan Percut. Keberlangsungan adaptasi dilihat dari strategi mengatasi melalui iuran dalam kelompok yang menjadi sarana untuk mewujudkan kepedulian antar sesama anggota, kerjasama dalam membantu sesama anggota, rasa kepercayaan, nilai dan norma yang berlaku dalam kelompok. Selain itu, kelompok nelayan juga membangun jaringan sosial dengan pemerintah desa dan dari Dinas Kelautan dan Perikanan dalam mengatasi kemiskinan kelompok nelayan dengan berbagai kegiatan.